Do Specialty Programs for Justice-Involved People With Mental Illness Exacerbate Stigma? - Eno Louden, Jennifer (Criminal justice and behavior, 2020)
Specialty mental health probation caseloads have shown promise in reducing recidivism for justice-involved people with mental illness. However, assignment to these caseloads may be stigmatizing due to labeling effects. We examined (1) whether assignment to specialty probation versus traditional probation is associated with greater internalized stigma among clients and (2) whether probation officers are the source of some of this stigmatization. As part of a multisite longitudinal study, 138 specialty probation clients and 148 similar clients from traditional probation rated their internalized stigma of mental illness, and officers rated their attitudes toward each of their supervisees. Specialty probation clients experienced more internalized stigma (d = .61) than traditional clients. Although both specialty and traditional officers held stigmatizing attitudes toward clients, only traditional officers’ attitudes were associated with clients’ internalized stigma. Probation officers from both types of agency may benefit from antistigma interventions to effectively work with clients with mental illness.